The Use of Snowball Technique in Teaching Writing Skill in EFL Classroom - Rina Indriani (VELES Voices of English Language Education Society, 2019)
This study aims at investigating the use of Snowball technique in teaching writing skill in EFL Classroom. Designed as pre-experimental research with pretest-posttest design, the sample of this research was 21 of 76 students of the tenth grade of SMK NW Pancor in the school year 2017-2018. Random sampling technique was used in determining the sample of the study. Writing test was the instrument used to collect the data. The data were then analyzed by using descriptive statistic and paired sample t-test to test the hypothesis. Based on the result of study, the mean score of the pre-test was 36.38 while in the post-test, it was 60.76; It means that the mean score of the post-test was higher than the mean score of pre-test. After submitting the data to a paired sample t-test, the present researcher found that the significance (2-tailed) value level of analyzed data was 0.00 which was lower than 0.05, so the alternative hypothesis (Ha) of this study was accepted. It implies that snowball technique was significantly effective in teaching writing recount text. It is suggested that English teacher use snowball technique as an alternative technique in teaching writing on recount text.